Increasing the Value of Telecom Operators with a Single EU Market - Silvia Serrano Calle (International Telecommunications Society (ITS), 2015)
In this paper we analyze the risks the European Telecom market is experiencing. Many economic disincentives to investing in infrastructure are related to the fact that market value of the companies can be lower than expected. Next Generation Networks (NGN) deployment require great amounts of capital but investing in new networks is not attractive for all players. The internet ecosystem is a much more complex scenario than the traditional telecommunications market and has changed the economic models. There are diverse regulatory approaches within the European Union (EU) nowadays. The Single European Market could be the solution to increase competitiveness and to rise the value of European Telecom Operators.
Keywords: G38; L25; L96; 330; Telecom operators; Next Generation Networks; EU Single Market; Regulatory risk